Avaliação experimental de destilação batelada em misturas etanol hidratado-cloreto de sódio por aquecimento com micro-ondas - Morais, Anderson dos Santos (2014)
The batch distillation is the basis for the design of continuous industrial units. The operation, which consists of separation of the more volatile substance present in a liquid-liquid mixture, might have a phenomenological representation through the balance of the phases with the application of thermodynamic models and consequential predictions of properties important to the operation. In this thesis, the batch distillation of ethanol blends hydrated and salt using radio frequency energy - RF (Microwave) as a power source for internal heat generation. Once the electromagnetic wave (Microwave) propagates on the physical environment as a function of the dielectric properties of the material and temperature, energy in radio frequency’s form is converted into heat making the material heats itself. For experimental development of this operation was necessary to build a distillation system using radio frequency with control pressure and temperature and data acquisition system called Distillation Microwave Unit, that has a cavity (reboiler) installed six emission sources microwave coupled to a column with sieve plates fourteen stages which offers the vapor from the top condenser to a total dividing the condensate into two streams, product or distillate and reflux. The experimental results were processed using the statistical method of central composite design and response surface. Experimental tests were conducted to verify the performance of the heating operation of water-alcohol mixtures microwave column batch separation stages in ethanol-water in the presence of sodium chloride at concentrations ranging from 0.16 to 1%, 8%. Was obtained in experiments ethanol with concentrations of 86% when. When related to energy consumption, has been a relative consumption of 1.59 kWh / kg of ethanol. These results showed good technical feasibility and economic viability is strong evidence, especially when the presence of electrolyte (NaCl), which improved the conversion of FR energy into heat. These results indicate a good alternative to the distillation process as it can increase the capacity of columns already installed. These results indicate a good alternative to the distillation process as it can increase the capacity of columns already installed.